Tissue Engineering Heart Valves – a Review of More than Two Decades into Preclinical and Clinical Testing for Obtaining the Next Generation of Heart Valve Substitutes - Dan SIMIONESCU; Marius Mihai HARPA; Agneta SIMIONESCU; Codrut OPRITA; Ionela MOVILEANU (Romanian Journal of Cardiology, 2021)
Well documented shortcomings of current heart valve substitutes – biological and mechanical prostheses make them imperfect choices for patients diagnosed with heart valve disease, in need for a cardiac valve replacement. Regenerative Medicine and Tissue Engineering represent the research grounds of the next generation of valvular prostheses – Tissue Engineering Heart Valves (TEHV). Mimicking the structure and function of the native valves, TEHVs are three dimensional structures obtained in laboratories encompassing scaffolds (natural and synthetic), cells (stem cells and differentiated cells) and bioreactors. The literature stipulates two major heart valve regeneration paradigms, differing in the manner of autologous cells repopulation of the scaffolds; in vitro, or in vivo, respectively. During the past two decades, multidisciplinary both in vitro and in vitro research work was performed and published. In vivo experience comprises preclinical tests in experimental animal model and cautious limited clinical translation in patients. Despite initial encouraging results, translation of their usage in large clinical scenarios represents the most important challenge that needs to be overcome. This review purpose is to outline the most remarkable preclinical and clinical results of TEHV evaluation along with the lessons learnt from all this experience.